Stability of the Casting Process According to the Method BOST - Borkowski, Stanislaw; Ingaldi, Manuela; Sygut, Piotr; Klimecka-Tatar, Dorota (Manufacturing Technology Journal, 2016)
Process stability is one of the factors determining high quality of the products. By stable process, operations conducted in order to produce a given product are repeatable, and at the same time products manufactured in such process are repeatable and theirs quality is predictable. In the article the BOST method was used to evaluate casting process stability. The research in from of a survey was conducted in one of the Polish foundry. The results were presented in form of 2x2 matrix. This matrix has two variables: process stability (X axis) and product quality (Y axis). Employees quite highly evaluated the process stability, and medium and low product quality. Which means that the research foundry is located in the B zone of the map of process stability, which is referred as "Fundamental changes in the process".
Keywords: Stability; Quality; Foundry; Foundry products; BOST